COOPERATION PROGRAMME AGREEMENT BETWEEN SILTERRA MALAYSIA SDN BHD and MALAYSIAN UNIVERSITIES IN MICROELECTRONIC DESIGN COLLABORATION Involving UNIVERSITI SAINS MALAYSIA UNIVERSITI MALAYA UNIVERSITI KEBANGSAAN MALAYSIA UNIVERSITI PUTRA MALAYSIA UNIVERSITI TEKNOLOGI MALAYSIA UNIVERSITI TEKNOLOGI MARA (Uitm) MULTIMEDIA UNIVERSITY - Universiti Malaya; Universiti Kebangsaan Malaysia; Universiti Sains Malaysia; Universiti Putra Malaysia; Universiti Teknologi MARA (UiTM); Multimedia University; Universiti Teknologi Malaysia; Silterra Malaysia Sdn. Bhd (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2006)
PRZSL